Zum Tigre - Voigt, Rainer (Aethiopica, 2008)
In Aethiopica 10 (2007) Gianfrancesco Lusini analysed and translated a passage from the new novel written in Tigre by Mohammad-Ali Ibrahim Mohammad. In very many cases I would prefer a different transcription and a different grammatical explanation, e.g. concerning the lengthening of consonants. Similarly the aʾa spelling of verbal forms in the A- and At-stems does not have its origin in the author’s “own convention” but it reflects an old orthographic and dialectal peculiarity.